Emergency remote education experiment amid COVID-19 pandemic - Toquero, Cathy Mae (IJERI: International Journal of Educational Research and Innovation, 2020)
Technology has been instrumental for efficient communication to counter the pandemic that the world is facing today. It also redefines how the educational system can proliferate the delivery of the teaching-learning process amidst COVID-19. This paper articulates the effectiveness of distance education, highlights the possible challenges in emergency remote education, and recommends emerging remote learning platforms along with policies for the utilisation of emergency remote teaching and protocols for the prevention of COVID-19 in Philippine learning institutions. The paper offers further research of innovative strategies, virtual learning experiences, and the transition from the physical classroom into an emergency remote education environment during the pandemic.